Bioethical Principles in Home-Based Virtual Care - Bendahan, Nathaniel; Chan, Sophy; Appireddy, Ramana (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
Virtual care (VC), a novel method of healthcare delivery, allows patients to stay home or at their preferred location and use personal internet-enabled devices to video-conference with their healthcare provider. VC is becoming ubiquitous across the US and Canada, particularly in response to COVID-19. In this paper, we discuss the benefits and limitations of VC and explore how it may align with or detract from the four principles of bioethics through case studies. Overall, we argue that it allows for greater accessibility, availability, and affordability of healthcare. However, certain clinical scenarios may not be suitable for VC, particularly when a thorough physical examination is required. While it may not always be clear when to use digital health technologies, it is prudent to have an honest and open conversation with the patient when offering this option.